2012
DOI: 10.3346/jkms.2012.27.8.864
|View full text |Cite
|
Sign up to set email alerts
|

Factors Related to Prehospital Time Delay in Acute ST-Segment Elevation Myocardial Infarction

Abstract: Despite recent successful efforts to shorten the door-to-balloon time in patients with acute ST-segment elevation myocardial infarction (STEMI), prehospital delay remains unaffected. Nonetheless, the factors associated with prehospital delay have not been clearly identified in Korea. We retrospectively evaluated 423 patients with STEMI. The mean symptom onset-to-door time was 255 ± 285 (median: 150) min. The patients were analyzed in two groups according to symptom onset-to-door time (short delay group: ≤ 180 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
34
3
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 27 publications
(29 reference statements)
11
34
3
1
Order By: Relevance
“…[15] While a study conducted in China confirmed about the mean delay of 23.58 hrs (SD=85.09) which is relatively higher than the present study. [14] The present study revealed the median duration of prehospital delay is eight hrs which is comparatively higher than other studies where lesser median delay times were reported in Korea (2.5 hrs), [16] Beijing (2.3 hrs), [17] and Chennai (three hrs). [18] The present study highlights the door to needle time was 54 min (SD=24) which is comparable to the study from South India and Beijing which depicted the median door-to-needle time were 75 and 82 min respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…[15] While a study conducted in China confirmed about the mean delay of 23.58 hrs (SD=85.09) which is relatively higher than the present study. [14] The present study revealed the median duration of prehospital delay is eight hrs which is comparatively higher than other studies where lesser median delay times were reported in Korea (2.5 hrs), [16] Beijing (2.3 hrs), [17] and Chennai (three hrs). [18] The present study highlights the door to needle time was 54 min (SD=24) which is comparable to the study from South India and Beijing which depicted the median door-to-needle time were 75 and 82 min respectively.…”
Section: Discussioncontrasting
confidence: 61%
“…In contrast to this, the previous studies have reported that the presence of diabetes was associated with increased delay. [1420] There was no significant difference in delay times with respect to the history of hypertension, history of smoking/alcoholism, or history of CAD. However, another study reported that history of MI/CAD was associated with reduced delay.…”
Section: Discussionmentioning
confidence: 95%
“…These findings were consistent with studies conducted by Momeni et al in Iran (9) and Peng et al (21) and Qian et al (14) in China who found that the type of transportation vehicle and the location of residency were associated with prehospital delay. However, some studies in Korea (13), Bushehr (10), and Bandar-Abbas (18) have found that residency and type of transportation vehicle were not associated with prehospital delay. Currently the EMS stations are mainly located within cities and then the delay time would be more in suburbs.…”
Section: Discussionmentioning
confidence: 99%
“…The reported mean time from onset of chest pain to hospital admission ranges from 273 ± 258 to 1302 ± 1524 minutes in different cities (9-11), and a delay over 180 minutes was observed in 70% of patients with AMI in Tehran City (11). The mean delay has been reported to be 185.2 ± 334.8 minutes in Turkey (12), 255 ± 285 minutes in Korea (13), and 1415 ± 5105 minutes in China (14). In addition, the median delay was 216 minutes in London (15), and 56.2% of patients presented to a hospital within 240 minutes of symptom onset in India (16).…”
Section: Introductionmentioning
confidence: 99%